COSEISMIC TEMPORAL CHANGES OF SLIP DIRECTION: THE EFFECT OF ABSOLUTE STRESS ON DYNAMIC RUPTURE - Guatteri M.; Spudich P. (My University, 1998)
We investigate the dynamics of rupture at low-stress level. We show that one main difference between the dynamics of high- and low-stress events is the amount of coseismic temporal rake rotation occurring at given points on the fault. Curved stations on exposed fault surfaces and earthquake dislocation models derived from ground-motion inversion indicate that the slip direction may change with time at a pointon the fault during dynamic rupture. We use a 3D boundary integral method to model temporal rake variations during dynamic rupture propagation assuming a slip-weakening friction law and isotropic friction. The points at which the slip rotates most are characterized by an initial shear stress direction substantially different from the average stress direction over the fault plane. We show that for a given value of stress drop, the level of initial shear stress (i.e., the fractional stress drop) determines the amount of rotation in slip direction. We infer that seismic events that show evidence of temporal rake rorations are characterized by a low initial shear-stress level with spatially variable direction on the fault (possibly due to changes in fault surface geometry) and an almost complete stress drop. Our models motivate a new interpretation of curved and cross-cutting striations and put new constraints on their analysis. The initial rake is in general collinear with the initial stress at the hypocenter zone, supporting the assumptions made in stress-tensor inversion from first-motion analysis. At other points on the fualt, especially away from the hypocenter, the initial slip rake may not be collinear with the initial shear stress, contradicting a common assumption of structural geology. On the other hand, the later part of slip in our models is systematically more aligned withi the average stress direction than the early slip. Our modeling suggests that the length of the straight part of curved striations is usually an upper bound of the slip-weakening distance is this parameter is uniform over the fault plane, and the direction of the late part of slip of curved striations should have more weight in the estimate of initial stress direction.